Sand dam water quality data - Parker, Alison; Quinn, Ruth (Cranfield University, 2018)
Water quality data collected in Kenyan sand dams in June and July 2016.
Keywords: Sand dam'; 'Water quality'; 'Kenya'; 'Hydrogeology'